PREPLANTING SETT TREATMENTS ON SPROUTING AND PERFORMANCE OF BAJRA NAPIER HYBRID GRASS Co (BN)5z - S.V. Varshini; C. Jayanthi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A field experiment was conducted in TNAU, Coimbatore during 2017 - 2018 to 2018 - 2019 to evaluate the effect of sett treatments on the growth, fodder yield, quality and economics of BN hybrid grass. The variety taken was CO (BN) 5 as a single bud in a RBD with 13 sett treatments and two replications. The result showed that higher sprouting, establishment percentage, growth attributes with higher number of tillers, green fodder (58.6 t/ha/cut) and dry fodder yield (12.6 t/ha/cut) were recorded with water soaking for 12 hours and 24 hours incubation (T ). Quality parameter viz., crude protein, crude fibre, crude fat and total ash content (%) showed non significant difference. Higher gross return (Rs.117222) and net return (Rs.79428) were recorded with water soaking for 12 hours and 24 hours incubation (T ). The lower cost of cultivation (Rs. 37794) was observed with water soaking for 12 hours and 24 hours incubation (T ).